Environmental Uncertainty as a Contingent Factor of Business Strategy Decisions: Introducing an Alternative Measure of Uncertainty - Dianwicaksih Arieftiara; Sidharta Utama; Ratna Wardhani (Australasian Accounting, Business and Finance Journal, 2017)
This study aims to examine a contingent factor of business strategy decisions, namely environmental uncertainty. The study applies secondary data as an alternative method to analyze technological uncertainty: a component of environmental uncertainty. To examine environmental uncertainty, this study develops an Environmental Uncertainty Index (EUI). Utilizing a sample of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period from 2009 to 2012 and a multinomial logistic regression, this study finds that the probability of a company pursuing a prospector strategy is greater than an analyzer strategy. Notwithstanding, the study fails to prove that the probability of a company opting for a defender strategy is greater than an analyzer approach. The findings suggest that the new measure of technological uncertainty is more applicable than the other existing measures. Furthermore, EUI measures the environmental uncertainty objectively, therefore, this new measure could be applied to future research. In general, this study broadens understanding concerning the relationship between business strategy and its contingent factors, namely environmental uncertainty.
Keywords: Business strategy; contingent factor; environmental uncertainty; Indonesia.